The origins of New Testament theology: a dialogue with Hans Dieter Betz - Hirsch-Luipold, Rainer; Calhoun, Robert Matthew (Wissenschaftliche Untersuchungen zum Neuen Testament, 2020)
Cover -- Title -- Preface and Acknowledgments -- Table of Contents -- List of Abbreviations -- Rainer Hirsch-Luipold and Robert Matthew Calhoun. Introduction -- Hans Dieter Betz. New Testament Theology: The Origins of a Concept -- Gerd Van Riel. Theology and Religiosity in the Greek Pagan Tradition -- Johan C. Thom. Theology and Popular Philosophy -- Rainer Hirsch-Luipold. Theo-logy in John and in Early Imperial Platonism -- Ulrich Luz †. Die biblische Tradition als Wurzelgrund neutestamentlicher Theologie: Eine Skizze -- Harold W. Attridge. The Beginnings of Christian Theology -- Samuel Vollenweider. Paläste und ihre Baupläne: Auf der Suche nach der Theologie des Neuen Testaments -- Hans Dieter Betz. The Reasons for Romans: Why Did Paul Write His Letter to the Romans? -- General Bibliography -- List of Contributors -- Indices -- A. Index of References -- B. Index of Modern Authors -- C. Index of Subjects.